An Analysis of Student' Difficulties in Vocabulary Mastery: A Case Study at English Club of SMAN 7 Kota Serang - Nurul Rahmawati; Nur Salamah Hidayatillah; Rosa Amelia (Lembaga Riset dan Inovasi Almatani, 2023)
The research's objectives were to identify the factors that contribute to students' difficulties mastering vocabulary and to learn about the challenges that students face in doing so. This study used a qualitative research design, and the researcher used interviews and questionnaires to collect data. Three students chosen by the teacher were interviewed for this study. This implies that students have the same chance of being selected as individual participants. Researchers used twenty participants in this study. Participants received a questionnaire from the researcher. since the goal of this study is to determine the challenge students face in mastering vocabulary. The English club students at SMAN 7 Kota Serang continue to struggle greatly with vocabulary acquisition. based on the word pronunciation, word spelling, and word meaning as revealed by the questionnaire and interview. Moreover, a variety of factors may contribute to the difficulties. There are a number of reasons why students struggle to master vocabulary: (1) mispronounced words compared to written words; (2) infrequent practice and interaction in English; and (3) incorrect word spelling or writing (4) A few words with related but distinct meanings, (5) Mispronunciations are frequently brought on by the dissimilarity of Indonesian and English phonemes.